Efektivitas Program Penanaman Mangrove Terhadap Kestabilan Lini Pantai Dan Kualitas Air Di Perairan Pantai Ciberi Kampung Enggros - Fransiskadianaturot; Thelly Sula Hendrina Sembor; Sarah Agustina Rumawak (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Effectiveness of Mangrove Planting Programs on Coastal Line Stability and Water Quality in Ciberi Beach Waters, Enggros Village. Mangrove forest degradation in Youtefa Bay has significantly declined from 511.24 Ha (1967) to 241.24 Ha (2008), impacting coastal stability and seawater quality. This study aims to analyze the effectiveness of mangrove planting programs on coastal line stability and water quality at Ciberi Beach, Enggros Village. The research employed a descriptive qualitative approach using weighting analysis (scoring) and the STORET method for water quality evaluation. Primary data were obtained through questionnaires administered to 88 respondents (47 community members, 25 NGOs, 16 government agencies) and water quality parameter measurements (pH, temperature, DO, TDS, salinity) at 4 location points. Results demonstrate very high program effectiveness across all indicators: ecological (community 95.74%, NGO 84.80%, agencies 77.00%), social (community 93.79%, NGO 86.72%, agencies 88.00%), economic (community 91.23%, NGO 83.84%, agencies 90.75%), and institutional (community 88.09%, NGO 76.80%, agencies 82.75%). STORET analysis showed good water quality in the morning (score -3) and moderately polluted conditions in the afternoon (score -12). The mangrove planting program has proven effective in maintaining coastal stability and improving coastal environmental quality. However, temporal variations in water quality parameters, particularly salinity and temperature fluctuations, require continuous monitoring. The study recommends expanding planting programs, implementing real-time water quality monitoring systems, strengthening spatial planning regulations, and developing community-based conservation economics to ensure long-term sustainability of mangrove ecosystems.